2016
DOI: 10.32677/ijch.2016.v03.i01.005
|View full text |Cite
|
Sign up to set email alerts
|

A study of modifiable risk factors for acute lower respiratory tract infections among under five children in a tertiary care hospital in Gulbarga, Karnataka

Abstract: Background: Acute respiratory infection includes any infection of the upper or lower respiratory system, as defined by the International Classification of Diseases. Acute respiratory infection is a leading cause of morbidity and mortality in under-five children in developing countries. Objective: This study was undertaken to identify various modifiable risk factors for acute lower respiratory tract infections (ALRI) in children aged from2 months to 5 years. Methodology: This hospital-based case–control study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…Study was conducted during Jan to Dec 2016 with estimated sample size of 400. The proportion of boys (52.7%) was greater than porportion of girls in the present study (47.3%), which is in line with similar studies conducted in other parts of India [11][12][13] In contrast to this, proportion of girls was more than boys in a study conducted by prajapati B in rural communities of Ahmedabad district [14] In our study, majority of the study population belonged to Hindu religion (86.2%) and similar observation was found in other studies [12,15] Factors causing indoor air pollution were among the main risk factors for ARI and it was found to be significantly associated in the present study. Similar association was found in WHO report 2008.…”
Section: Discussionsupporting
confidence: 92%
“…Study was conducted during Jan to Dec 2016 with estimated sample size of 400. The proportion of boys (52.7%) was greater than porportion of girls in the present study (47.3%), which is in line with similar studies conducted in other parts of India [11][12][13] In contrast to this, proportion of girls was more than boys in a study conducted by prajapati B in rural communities of Ahmedabad district [14] In our study, majority of the study population belonged to Hindu religion (86.2%) and similar observation was found in other studies [12,15] Factors causing indoor air pollution were among the main risk factors for ARI and it was found to be significantly associated in the present study. Similar association was found in WHO report 2008.…”
Section: Discussionsupporting
confidence: 92%
“…These were: child's age, child's sex, child received Bacille, Calmette Guerin (BCG) in the last 6 months, child received Vitamin A in the last 6 months, child received intestinal parasite in the last 6 months, mother's age, mother's employment status, mother's education level, father's educational level, wealth status, residence, household size, source of drinking water, type of toilet facility, and type of cooking fuel. The variables were chosen based on their availability in the DHS dataset and previous studies (Gebertsadik et al, 2015, Jackson et al, 2013; Arun et al, 2014, Mirji et al, 2016; Prajapati, Talsania, Lala & Sonalia, 2012) which have found them as influential determinants of ALRIs among children.…”
Section: Methodsmentioning
confidence: 99%
“…In relation to ALRIs, some studies have been conducted in sub-Saharan African countries such as Nigeria (Adesanya & Chiao, 2017; Akinyemi & Morakinyo, 2018), Rwanda (Harerimana et al, 2016), Ethiopia (Alemayehu et al, 2014; Gebertsadik et al, 2015), Cameroun (Tazinya et al, 2018) and Ghana (Jones et al, 2016; Sumaila & Tabong, 2018). Some of these studies conducted in sub-Saharan and other settings on ALRIs have been at the micro level using smaller samples (see Chen et al, 2014; Ramani, Pattankar, & PuttAhonnAPPA, 2016, Cardoso, Coimbra & Werneck, 2013, Fekadu, Terefe, & Alemie, 2014; Alemayehu et al, 2014; Arun, Gupta, Sachan, & Srivsatava, 2014; Mirji, Shashank, & Shrikant, 2016; Prajapati, Talsania, Lala & Sonalia, 2012). The results of such studies may not be applicable to all children under-five due to the unrepresentative nature of samples used.…”
Section: Introductionmentioning
confidence: 99%
“…Acute respiratory infection (ARI) is one of the most frequent childhood diseases that remains a huge public health problem globally [1][2][3][4]. Sub-Saharan Africa (SSA) is the region with the highest child mortality in the world [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%